KARAKTERISTIK FISIS TELUK AMBON MENGGUNAKAN PEMODELAN HIDRODINAMIKA 3 DIMENSI - Sabrina, Purwanti Lelly (Universitas Methodist Indonesia, 2023)
Outer Ambon Bay (TAL) and Inner Ambon Bay (TAD) are part of Ambon Bay, which are semi-enclosed waters bounded by a narrow threshold. The characteristics of TAL are strongly influenced by the condition of the Banda Sea waters. Physical characteristics in the Banda Sea are influenced by the phenomenon of upwelling during the southeast season which brings water masses with high salinity and low temperature into the TAL. The condition of Ambon Bay is also influenced by the density gradient and tidal upwelling phenomenon. A 3-dimensional hydrodynamic modeling simulation was conducted to see the tidal upwelling phenomenon that affects the physical dynamics in Ambon Bay. The model simulation time was adjusted to the southeast season, namely June 1 - October 31, 2015. Comparison of simulated tidal elevation values with observation data showed a Root Mean Square Error (RMSE) value of 0.11 m with a correlation coefficient of 94.3%. The distribution of water temperature from the model simulation shows the same value as the satellite image data, which is 26°C.